Study effect of plant extraction for Cuscuta europaea (Dodder) against two species of bacteria Staphylococcus aureus and Escherichia coli - Abdullah, Jasim A.; Hammadi, Amer Ali; Hakem, Russell; Hatef, Zahra; Hussein, Noor (Journal of Contemporary Medical Sciences, 2016)
Objective: The goal of this study is focused on the effect of crude extract of Cuscuta europaea plant and compared with Amoxicillin drug, and then we showed these effects on Staphylococcus aureus and Escherichia coli. The analysis shows that the side effect of drug is high on human. We try to find the alternative antimicrobial to treat the bacterial infection. This study focuses on two treatments to inhibit the growth of two species of bacteria that are Amoxicillin as drug and Cuscuta eurooaea as extract until show the activity antimicrobial of these amount on bacteria. Methods: The current study included Cuscuta europaea as extract and Amoxicillin as drug and two species of the bacteria Staphylococcus aureus and Escherichia coli. This study has been investigated to show the antimicrobial activity of plant extract and drug on the bacteria. Results: During this study, the results reveal that the activity of antimicrobial of extract plant was higher than Amoxicillin on Staphylococcus aureus but the both Amoxicillin and extract did not have any effect on Escherichia coli in each concentration. And we showed the best result recorded in concentration 20 mg/ml of extract plant when compared with amoxicillin drug. Conclusion: There are no significant differences between the concentration of plant extract of bacteria, and we showed the plant extract have a high effect on gram positive bacteria but do not have any effect on gram negative bacteria.